Управління організаційним розвитком підприємства на основі архітектурної моделі управління бізнесом - Коренюк, Людмила Володимирівна; Чернявський, Марк В. (Міжнародний гуманітарний університет, Київ, 2021)
UKR: У статті визначено особливості побудови системи управління організаційним розвитком підприємства на основі архітектурної моделі управління бізнесом. Обґрунтовано питання розроблення архітектури організаційного розвитку у постійно мінливому ландшафті бізнес-процесів у контексті архітектурного підходу до управління підприємством. Запропоновано використати методику TOGAF для проектування, планування, впровадження, управління ор-ганізаційним розвитком підприємства. Побудовано діаграму вигоди (Benefit Diagram) управління організаційним розвитком підприємства як складової частини методики TOGAF. Визначено, що управління організаційним розвитком повинно відбуватися на всіх рівнях архітектури підприємства. Перспективою подальшого розвитку є розроблення дорожньої карти (road map) для уточнення дій стосовно розроблення цільової архітектури бізнес-моделі.

ENG: The article identifies the features of building a management system for organizational develop-ment of the enterprise on the basis of the architectural model of business management. Synchronization of stra¬tegic and operational tasks of business with organizational development is determined. The issue of developing the architecture of organizational development in the constantly changing landscape of business processes in the context of the architectural approach to enterprise management is substantiated. It is proposed to use the TOGAF methodology for design, planning, implementation, management of organizational development of the enterprise. The Benefit Diagram of management of organizational development of the enterprise as a component of TOGAF methodology is constructed. A hierarchical structure of enterprise architecture is built, consisting of seven levels. The business architecture is based on process management, and business management systems (BPM) are used to develop it. BPM monitors business processes, collects valuable performance statistics, and provides a basic set of business process performance reports. Based on them, you can set key performance indi¬cators (KPIs), which will be interrelated with a balanced scorecard (BSC). It is determined that the management of organizational development should take place at all levels of enterprise architecture. It is proved that the construction of the model allows to constantly change the needs for information in order to form an adequate organizational infrastructure of the enterprise and creates opportunities to determine the architectural model of business development. Changes in business architecture must take place continuously at the operational, tactical and strategic levels. This requires the improvement and synchronization of information flows that support busi¬ness processes, improving the quality of methods, models and knowledge systems accumulated in management decisions. The development of the model becomes possible under the condition of continuous monitoring and audit of the organizational infrastructure. Prospects for further development are the development of a road map (road map) to clarify actions for the development of the target architecture of the business model.
Management of Organizational Development of the Enterprise on the Basis of the Architectural Model of Business Management
L Korenyuk: ORCID 0000-0003-3187-3288
Keywords: організаційний розвиток; управління; архітектурна модель; артефакт; organizational development; management; architectural model; artifact; КФЕБ